Unexpected morphological modifications in high moisture extruded pea-flaxseed proteins: Part I, topological and conformational characteristics, textural attributes, and viscoelastic phenomena. (March 2023) - Riazi, Fatemeh; Tehrani, Mostafa Mazaheri; Lammers, Volker; Heinz, Volker; Savadkoohi, Sobhan
Abstract: The present study aims at gaining a better understanding on the structuring mechanisms and textural attributes of pea protein isolate influenced by the addition of flaxseed protein concentrate (FPC) during high moisture extrusion. Overall results mainly indicated amended structure and significantly ( P < 0.05 ) less compacted texture at 8% of FPC content. At controlled heating and shearing conditions, anisotropy occurred with an increased level of FPC following remarkable modification in protein-protein interactions for extruded samples. The comparison revealed that although the basic chemical compositions were close to their native structure, the functional properties were affected by the increase in FPC content within the domain structure of filaments. Following this, the expressible moisture and cooking yield were increased and textural properties, such as cutting force and elasticity, were decreased upon the addition of FPC. In addition, mechanical and thermal findings were successfully plotted in the KBKZ model and hypothetically represented that the protein aggregates can be formed and structured in a different format in the added-FPC samples due to the hydrophobicity nature of globulin proteins in flaxseed. Scanning electron microscopic observations then proved the formation of structured macromolecules with small and large air holes entrapped in the domain orients. Part I of this study allowed for a deeper understanding of composite effects in structuring the plant-based meat alternatives and their physicochemical properties. It emphasized the importance of domain structure of extruded plant proteins in the development of satisfactory meat analogs. Graphical abstract: Image 1 Highlights: Using FPC in PPI extrudate significantly altered viscoelastic traits. Flaxseed and pea protein conformations are structurally altered under HME. Flaxseed globulin proteins partially maintains its native conformation. Correlations among the molecular entanglement were modeled using KBKZ . FPC is a promising additive to improve the texturization in meat analogs.